Penerapan matematika pada bidang perbankan - Putri, Marizcha Lutfiana (Maliki Interdisciplinary Journal, 2024)
This article discusses the application of mathematics in banking, starting from basic economic mathematical concepts such as functions, sets and number operations. In banking, mathematics is used to calculate interest and manage deposits. Case studies of interest calculations for checking and savings deposits demonstrate practical applications of this concept, including the lowest balance, average balance, and daily balance methods. Time deposits and certificates of deposit are also analyzed in terms of interest calculation and payments. The use of mathematics allows banks to make accurate predictions and optimize the management of customer funds. This article emphasizes the importance of mathematics in solving economic and banking problems efficiently.